The Relationship between Economic Factors Influencing Afghan Migration: An Analysis of Economic Crises and Employment Opportunities (Salam International Academic Journal, 2025)
This paper investigates the economic factors influencing Afghan migration, with a particular focus on the role of economic crises and employment opportunities in intensifying or reducing migration trends. Drawing on migration theories and the political economy framework, the study explores the relationship between economic fluctuations, financial crises, labor market conditions, and individuals’ decisions to leave the country.A mixed-methods research design was adopted, combining both qualitative and quantitative approaches. The methodology includes a literature review, semi-structured interviews with subject-matter experts, and statistical analysis of secondary data from both international and domestic sources.The findings indicate that key drivers of Afghan migration include economic crises such as inflation, currency devaluation, and high unemployment, along with a persistent lack of job opportunities. These economic pressures significantly contribute to individuals’ motivation to migrate. Based on the evidence, it is clear that economic instability and limited employment prospects are central factors in shaping migration patterns.To address these challenges, the study recommends that policymakers and relevant institutions invest in building robust economic infrastructure, reform the education system, and combat administrative corruption. Such measures can foster greater social stability and reduce the rate of outward migration.The research contributes to the broader understanding of migration dynamics and provides a foundation for more comprehensive studies and policy development in the fields of migration and economic resilience. The paper concludes by outlining practical recommendations for mitigating the negative impact of economic factors on migration flows.
Keywords: Migration; Economic Crisis; Job Opportunities; Afghanistan; Economic Analysis